Building a Sustainable Maritime Workforce: The Role of Leadership and Education in Enhancing Safety and Environmental Responsibility - Chanra Purnama; Riyanto Riyanto; Larsen Barasa; Titis Ari Wibowo; Cris Kuntadi; Meilinasari Nurhasanah Hutagaol; Marudut Bernadtua Simanjuntak (International Journal of Management, Accounting & Finance (KBIJMAF), 2025)
Sustainability is becoming a critical focus within maritime education, leadership, and workforce development as the industry adapts to evolving environmental regulations and safety imperatives. This research explores the integration of sustainability principles in maritime training programs and leadership frameworks, addressing gaps in workforce development and the application of sustainable practices. The study provides original insights by examining qualitative perspectives from maritime professionals, educators, and graduates, complementing previous research by offering empirical evidence on sustainability in vocational education. The primary objective was to investigate how sustainability is embedded within maritime education and leadership, focusing on its role in fostering safety cultures and environmental responsibility. The research employed a qualitative approach, combining systematic literature review (SLR) with interviews and questionnaires involving ten maritime stakeholders. The results indicate a strong alignment between sustainability goals and educational frameworks, with leadership emerging as a key driver of sustainable practices. While overall scores reflect significant progress, the findings highlight areas for enhancing workforce development, particularly in reinforcing environmental responsibility. The study underscores the importance of leadership in shaping sustainable organizational cultures and advocates for more comprehensive, sustainability-focused curricula in maritime vocational programs. The conclusions emphasize the need for greater collaboration between educational institutions and industry leaders to ensure cohesive progress in sustainability adoption. This research contributes to shaping a future maritime workforce that is technically proficient, environmentally conscious, and safety-driven.